2016
DOI: 10.5702/massspectrometry.a0051
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Derivatization with Structures Having High Proton Affinity for Discrimination between Leu and Ile Residues in Peptides by High-Energy Collision-Induced Dissociation

Abstract: De novo sequencing is still essential in the identi cation of peptides and proteins from unexplored organisms whose sequence information is not available. One of the remaining problems in de novo sequencing is discrimination between Leu and Ile residues. e discrimination is possible based on di erences in side chain fragmentation between Leu and Ile under high-energy collision-induced dissociation (HE-CID) conditions. However, this is observed only when basic residues, such as Arg and Lys, are present near the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Furthermore, Ile has a methyl group at the β-carbon in its side chain, while Leu has only one hydrogen atom at the β-carbon. The structural difference also makes Ile’s side chain more prone to breaking than Leu’s . Subsequently, the detection performance of DHT, DHB, and CHCA was evaluated using MALDI-MS in positive-ion mode for a mixture containing 20 protein AAs with DHT, DHB, and CHCA as the MALDI matrices, respectively (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Ile has a methyl group at the β-carbon in its side chain, while Leu has only one hydrogen atom at the β-carbon. The structural difference also makes Ile’s side chain more prone to breaking than Leu’s . Subsequently, the detection performance of DHT, DHB, and CHCA was evaluated using MALDI-MS in positive-ion mode for a mixture containing 20 protein AAs with DHT, DHB, and CHCA as the MALDI matrices, respectively (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The structural difference also makes Ile's side chain more prone to breaking than Leu's. 50 Subsequently, the detection performance of DHT, DHB, and CHCA was evaluated using MALDI-MS in positive-ion mode for a mixture containing 20 protein AAs with DHT, DHB, and CHCA as the MALDI matrices, respectively (Figure 2). The results showed that the DHT matrix detected all individual AAs from the mixed solution, whereas DHB and CHCA only detected 8 and 11 AAs, respectively (Figure 2D).…”
Section: Maldi-tof Ms Analysis Of Standard Aasmentioning
confidence: 99%
“…10) Since Gmb contains a carboxyl group, its introduction can be achieved by formation of an amide bond with the amino group of peptides using condensation reagents. DMT-MM has been widely used for amide bond formation between various compounds, due to its high reactivity superior to other reagents such as carbodiimide or NHS.…”
Section: Resultsmentioning
confidence: 99%
“…Grignard synthetic method reaction attempts with reaction conditions and modifications to produce 2,2-dimethyl-5-(5-methylhex-1-yn-3-yl)-1,3-dioxane-4,6-dione (12) following the procedure outlined by Krabbe. 71 (16). Conditions and procedures are modifications of procedures outlined by Bigi, Dumas and Sobrinho.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…15 Another CD reagent that contains a highly ionizable group is 4-amidinobenzoic acid (Aba) as seen in Figure 1.3. 16 This reagent was highly successful at increasing sensitivity and generating d-ions of the peptide to allow differentiation of leucine and isoleucine residues. 16 However, derivatization reactions with peptides occurred overnight at room temperature thus quick analysis of analytes was limited.…”
Section: Reagents Introducing Easily Ionizable Groupsmentioning
confidence: 99%